Pengaruh Souvenir Olahan Susu terhadap Pendapatan Masyarakat di Kabupaten Bandung Barat - Dasipah, Euis; Wirakusuma, Reiza Miftah (Universitas Pendidikan Indonesia, 2017)
This research aimed to know the influence of animal feed given to cattle towards the dairy products, income, and small breeders income. The tourism being induced in this dairy products were souvenirs for tourists. Method of the survey were dairy farmers of KPSBU Member in the West Bandung Regency, through snowball sampling on 8 people with a total of 62 cattle breeders. Analysis test has been done for validity, reliability tests, and correlation analysis test andÂ also test of track analysis. Testing on research data showed that all research variables are valid and reliable, the correlation between variables also showed a positive relationship. Path analysis produce: 1) the feed given to cattle amounted toÂ 63.1% against dairy products affects, 2) the feed given to cattle has a positive effect against breeders income either directly or indirectly, 3) dairy products also has a positive effect against breeders income either directly or indirectly, and 4) the feed given to cattle and dairy products affect of 93% against breeders income.